Evaluation of immunosuppression protocols for MHC-matched allogeneic iPS cell-based transplantation using a mouse skin transplantation model - Tomoki Kamatani; Ryo Otsuka; Tomoki Murata; Haruka Wada; Takeshi Takahashi; Akihiro Mori; Soichiro Murata; Hideki Taniguchi; Ken-ichiro Seino (BMC, 2022)
Abstract Background Off-the-shelf major histocompatibility complex (MHC)-matched iPS cells (iPSC) can potentially initiate host immune responses because of the existence of numerous minor antigens. To suppress allo-immune responses, combination of immunosuppressants is usually used, but its efficacy to the allogeneic iPSC-based transplantation has not been precisely evaluated. Methods Three transplantation models were used in this study; MHC-matched, minor antigen-mismatched mouse skin or iPSC-graft transplantation, and fully allogeneic human iPSC-derived liver organoid transplantation in immune-humanized mice. The recipients were treated with triple drugs combination (TDC; tacrolimus, methylprednisolone, and mycophenolate mofetil) or co-stimulatory molecule blockade (CB) therapy with some modifications. Graft survival as well as anti-donor T and B cell responses was analyzed. Results In the mouse skin transplantation model, immunological rejection caused by the minor antigen-mismatch ranged from mild to severe according to the donor-recipient combination. The TDC treatment could apparently control the mild skin graft rejection when combined with a transient T cell depletion, but unexpected anti-donor T or B cell response was observed. On the other hand, CB therapy, particularly when combined with rapamycin treatment, was capable of attenuating both mild and severe skin graft rejection and allowing them to survive long-term without any unfavorable anti-donor immune responses. The efficacy of the CB therapy was confirmed in both mouse and human iPSC-derived graft transplantation. Conclusions The findings suggest that the CB-based treatment seems suitable to well manage the MHC-matched allogeneic iPSC-based transplantation. The TDC-based treatment may be also used to suppress the rejection, but screening of its severity prior to the transplantation seems to be needed.